Reconfiguring Journalistic Authority as a Socio-Technical Information System in Platformized News Environments (Architecture Image Studies, 2026)
Digital platforms increasingly operate as socio-technical information systems that reorganize how information is produced, distributed, and legitimized. This article examines how journalistic authority is reconfigured when journalists operate as individual news brands embedded within platform-based information systems such as YouTube and Instagram. Drawing on in-depth interviews with former institutional journalists and qualitative analysis of their platform-native news content, the study explores how professional legitimacy is constructed through algorithmic visibility, datafied performance metrics, and platform governance mechanisms. The findings demonstrate that journalistic authority is displaced from organizational information systems to individual actors whose credibility emerges through the interaction of professional norms, audience-mediated trust, and algorithmic ranking systems. By conceptualizing individual news brands as human-centered information systems operating within platformized environments, this study contributes to information systems research on platform governance, socio-technical infrastructures, and the transformation of professional authority in the digital era.